Door beeldhouwers gemaakt : Vito Acconci, Carl Andre, Aycock Alice, Lynda Benglis, Joseph Beuys, Ger Van Elk, Barry Flanagan, Gilbert & George, Eva Hesse, Bryan Hunt, Richard Long, Gordon Matta-Clark, Bruce Nauman, Giuseppe Penone, Cornelius Rogge, Ulrich Rückriem, Richard Serra, Joel Shapiro, Charles Simonds, Richard Tuttle, Carel Visser, Jackie Winsor. - Van Beijeren, Geert; Dippel, Rini; Mignot, Dorine; Stedelijk Museum, Amsterdam (Amsterdam : Stedelijk Museum Amsterdam, 1978)
Acconci, Vito ; Andre, Carl ; Aycock, Alice ; Benglis, Lynda ; Beuys, Joseph ; Van Elk, Ger ; Flanagan, Barry ; Gilbert & George ; Hesse, Eva ; Hunt, Bryan ; Long, Richard ; Matta-Clark, Gordon ; Nauman, Bruce ; Penone, Giuseppe ; Rogge, Cornelius ; Rückriem, Ulrich ; Serra, Richard ; Shapiro, Joel ; Simonds, Charles ; Tuttle, Richard ; Visser, Carel ; Winsor, Jackie
Stedelijk Museum Amsterdam, 14 september - 5 november 1978
kunstcatalogus